Redundancy of macrobenthic functional traits boosts resilience to a simulated heatwave - Orlando Lam-Gordillo; Emily J. Douglas; Sarah F. Hailes; Andrew M. Lohrer (PLoS ONE, 2026)
Climate change is affecting ecosystems worldwide. Ocean temperature is increasing, leading to more frequent and intense extreme weather events such as heatwaves (HWs) and marine heatwaves (MHWs). These extreme temperature events can affect marine biodiversity, the relative success of different life history strategies, and the structure and function of whole ecological communities. Understanding the effects of HWs on marine communities and the mechanisms that enable marine communities to resist and recover from heat stress has become a research priority. Here, we investigated the effects of a simulated HW on macrobenthic communities and their functional traits in intertidal estuarine sediments using a novel in-situ seafloor warming experiment with two heatwave duration treatments. Our results revealed that the simulated HW influenced macrobenthic abundance and diversity, yet, functional traits and functional metrics were less affected. This suggests resilience to the simulated HW related to redundancy of macrobenthic functional traits. The idiosyncratic responses observed in our study reflects the complex and context-dependent macrobenthic responses to thermal extremes. Our findings suggest that maintaining functional trait diversity and redundancy could be key for boosting ecosystem resilience under increasing climatic extremes.